2016
DOI: 10.1177/2058460115604009
|View full text |Cite
|
Sign up to set email alerts
|

Shear elastic modulus is a reproducible index reflecting the passive mechanical properties of medial gastrocnemius muscle belly

Abstract: BackgroundPassive mechanical properties are important in muscle function because they are related to the muscle extensibility. Recently, the assessment of muscle shear elastic modulus using shear-wave elastographic (SWE) imaging was developed. However, reliability and validity of shear elastic modulus measurements during passive stretching remain undefined.PurposeTo investigate the reproducibility and validity of the shear elastic modulus measured by SWE imaging during passive stretching.Material and MethodsTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
(50 reference statements)
3
17
1
Order By: Relevance
“…Because of the within-muscle variability of the shear modulus, it is important that the measurements are performed within muscle region such that results can be compared between participants and studies. For the GM muscle, reliability was similar to that obtained by Nakamura et al (2016) (CV between 5 and 10%) and was slightly better than that reported by Freitas et al (2015) (SEM of 14.8 kPa for GM at 75% of ankle maximum ROM in dorsiflexion). The novelty of the present study is the assessment of the inter-day reliability of the other plantar flexor muscles.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Because of the within-muscle variability of the shear modulus, it is important that the measurements are performed within muscle region such that results can be compared between participants and studies. For the GM muscle, reliability was similar to that obtained by Nakamura et al (2016) (CV between 5 and 10%) and was slightly better than that reported by Freitas et al (2015) (SEM of 14.8 kPa for GM at 75% of ankle maximum ROM in dorsiflexion). The novelty of the present study is the assessment of the inter-day reliability of the other plantar flexor muscles.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies estimated the passive behavior of plantar flexors by measuring the shear modulus of the gastrocnemius medialis (GM) muscle during passive dorsiflexion using shear wave elastography (e.g. Ma€ ısetti et al 2012;Chernak et al 2013;Hug et al 2013;Chino & Takahashi, 2015;Freitas et al 2015;Hirata et al 2015Hirata et al , 2016Taniguchi et al 2015;Nakamura et al 2016). To our knowledge, only two studies completed the investigation on the three heads of the triceps surae [GM, the gastrocnemius lateralis (GL) and the soleus (SOL)] (Hirata et al 2015(Hirata et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…TUG and FSST are known as the major methods for evaluating dynamic balance, and they are well correlated with gait speed . A previous study reported that the elasticity of the MG was related to its flexibility . Menz et al showed that ankle flexibility measured on the modified weight‐bearing lunge test was an independent predictor of dynamic balance ability and gait speed .…”
Section: Discussionmentioning
confidence: 99%
“…18,27 A previous study reported that the elasticity of the MG was related to its flexibility. 11 Menz et al showed that ankle flexibility measured on the modified weight-bearing lunge test was an independent predictor of dynamic balance ability and gait speed. 12 Furthermore, several studies reported that improvements of hip and ankle flexibility were associated with increased gait speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation